fo017711: Bond Moyson Oudenaarde
"Kleurfoto van het bestuur van Bond Moyson-Oudenaarde, 1970. Zittend v.l.n.r.: Jozef Velghe, Liban De Jonghe, Marie Decordier, Marcel Vandercruyssen, Emiel Messiaen, Armand De Puydt. Staand v.l.n.r.: Victor Eggermont, Daniel Clepkens, Herman Blommaert, Henri Michels, Georges De Waele, Edwin Thomaes, Marc Rogge, Leon Hennebert. FULL TEXT AVAILABLE AT AMSAB-ISH"